AN ANALYSIS ON THE ERRORS IN USING SIMPLE PAST TENSE MADE BY STUDENTS AT CLASS VIII-C IN SMP TRISAKTI I MEDAN - Situmorang, Roganti; Saragih, Erikson; Tarigan, Karisma E. (Kairos English Language Teaching Journal, 2020)
This research is aimed to analysis on the errors in using simple past tense made by students at class VIII in SMP Trisakti I Medan. The subject of this research of the eighth grade students of SMP Trisakti I Medan. The method used in this study was descriptive analysis method to describe studentsâ€™ errors and analyze the data by using formula:Â Â x 100 %,Â P= Â percentage, F= Frequency of error made, N= Total of studentsâ€™ errors. The data was taken from the test: it was written test. The result of the errors analysis process showed that studentsâ€™ committed error into four types: omission,Â addition, misformation, and misordering. From the frequency of each error types, showed that there are 218 errors made by the students.the most frequent error made by students is Misformation which consists of 160 errors or 73,3%,Â it is followed by omission with 32 errors or 14,7%. The next is addition which consists of 15 errors or 6,7%. And the last is misordering with 11 errors or 5%.